To find the product of the two matrices, we will multiply them according to the rules of matrix multiplication.
Let: \[ A = \begin{pmatrix} -2 & 0 \ 3 & -4 \end{pmatrix}, \quad B = \begin{pmatrix} 0 & 1 \ -3 & -1 \end{pmatrix} \]
The product \( AB \) will be calculated to form a new matrix \( C \):
\[ C = AB = \begin{pmatrix} c_{11} & c_{12} \ c_{21} & c_{22} \end{pmatrix} \]
Where:
- \( c_{11} \) is the dot product of the first row of \( A \) and the first column of \( B \).
- \( c_{12} \) is the dot product of the first row of \( A \) and the second column of \( B \).
- \( c_{21} \) is the dot product of the second row of \( A \) and the first column of \( B \).
- \( c_{22} \) is the dot product of the second row of \( A \) and the second column of \( B \).
Let's calculate each element in \( C \):
- Calculating \( c_{11} \):
\[ c_{11} = (-2)(0) + (0)(-3) = 0 + 0 = 0 \]
- Calculating \( c_{12} \):
\[ c_{12} = (-2)(1) + (0)(-1) = -2 + 0 = -2 \]
- Calculating \( c_{21} \):
\[ c_{21} = (3)(0) + (-4)(-3) = 0 + 12 = 12 \]
- Calculating \( c_{22} \):
\[ c_{22} = (3)(1) + (-4)(-1) = 3 + 4 = 7 \]
Putting it all together, we get the product matrix \( C \):
\[ C = \begin{pmatrix} 0 & -2 \ 12 & 7 \end{pmatrix} \]
Thus, the product of the two matrices is:
\[ \begin{pmatrix} 0 & -2 \ 12 & 7 \end{pmatrix} \]